(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article examines the issues: legal and sociological concept families; The main tasks of the family; family protection by society and government family law of foreign countries, etc. The concept of family law; the role and place of family law in the legal system; principles of family law; a system of family law